2021
DOI: 10.52965/001c.24927
|View full text |Cite
|
Sign up to set email alerts
|

Zolpidem: Efficacy and Side Effects for Insomnia

Abstract: Insomnia is linked to fatigue, distractibility, mood instability, decreased satisfaction, and overall decreased quality of life. Optimal therapy can aid patients in returning to baseline and increase their quality of life. Zolpidem is a helpful drug for the treatment of insomnia in conjunction with cognitive-behavioral therapy. When prescribed to elderly patients, the dose should be adjusted to account for their slower drug metabolism. Still, zolpidem is considered a reasonable choice of therapy because it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 47 publications
0
22
0
11
Order By: Relevance
“…In this study, we examined the effect of 1 month of zolpidem, although various studies have reported side effects such as the risk of suicide, rebound insomnia, falls, hip fractures, etc. in long-term use or with high doses of this drug, and this point should be considered in the administration of zolpidem ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined the effect of 1 month of zolpidem, although various studies have reported side effects such as the risk of suicide, rebound insomnia, falls, hip fractures, etc. in long-term use or with high doses of this drug, and this point should be considered in the administration of zolpidem ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, medication use and choice is an important concept in medical care because drugs can have many possible adverse effects on multiple organ systems. Non-steroidal anti-in ammatory drugs, which are antipyretic, anti-in ammatory, and analgesic drugs, and the drugs commonly used for insomnia have been reported to cause many side effects (9,10). In addition, long-term administration of certain drugs, such as opioid analgesics, is associated with high rates of addictive-like behavior and poor recovery outcomes (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Z-drugs have been linked to an increased risk of falls and certain central nervous system (confusion, dizziness, daytime sleepiness, etc.) [ 10 , 17 ].…”
Section: Introductionmentioning
confidence: 99%